#TITLE_ALTERNATIVE# - B. M. ADITYA PUTRA RACHMAT (NIM : 12213040), R.
Injection gas requirement of oil wells known by Gas Lift Performance Curve (GLPC) which shows the correlation between oil production rate and injection gas rate. Inefficient gas lift injection rate allocation can affect the efficiency of production wells. This affects net cash flow (NCF) obtained which is affected by oil production that will affect revenue, gas lift injection rate that will affect cost, and efficient gas lift injection rate can be used as sale gas that will affect revenue too. In this study, simulations were performed with modeling that included production systems and surface facilities using GAP while each production wells that included reservoir systems to the surface were performed with modeling using Prosper. With simulations using these two software, predictions of oil production with various numbers of gas injection rates will be generated. Then, an economic aspect is evaluated using simple economic variables so we know the optimal gas injection rate by considering the technical and economic aspects. The result of this study shows that technically to obtain maximum oil production, gas lift injection rate required is 1.38 MMSCFD for well X-9 with production 130.21 STB, 0 MMSCFD for well X-10 with production 140.4 STB, and for well X-1 and X-5 canÃ‚Â’t be determined due to absence of an optimum point until gas lift injection rate 10 MMSCFD. While economically to obtain maximum NCF, gas lift injection rate required is 0 MMSCFD for well X-1 with oil production 110037 STB and NCF 3.39 millions US$, 0 MMSCFD for well X-5 with oil production 384266 STB and NCF 12.14 millions US$, 0.7 MMSCFD for well X-9 with oil production 470880 STB and NCF 14.33 million US$, and 0 MMSCFD for well X-10 with production 511429 STB and NCF 16.1 millions US$ thus the total gas lift injection rate required is 0.7 MMSCFD to obtain 1476612 STB and NCF 45.96 millions US$ for field X.